Modelo propuesto para la implementación de la metodología smed en una empresa de alimentos de Santiago de Cali (2017)
This article proposes to apply the SMED method in the process of changing molds in an ice cream cones machine, owned by a food company located in Santiago de Cali. Currently, the flexibility of the processes is a fundamental element to improve productivity, a factor that could become a source for generating competitive advantages in the market. The study methodology consists in the identification of one of the most used machines in the manufacture of cones, through analysis of lost times and efficiency; once the device has been identified, the most significant change is defined and in this way the findings obtained by means of the technique are analyzed, and the proposal to be considered in its implementation is presented, which serves as the basis for improving the other machines the production line. There are applications of the SMED in processes of change of molds in injection molding machines, but it is unknown if this method has explicitly focused on the elaboration of cones; therefore, this article might work as a reference for other companies in which the application of the SMED may be done in an identical or similar way.